2003
DOI: 10.1021/es034046e
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic and Geochemical Assessment of in Situ Biodegradation of Chlorinated Hydrocarbons

Abstract: Currently there is no in situ method to detect and quantify complete mineralization of chlorinated hydrocarbons (CHCs) to CO 2 . Combined isotopic measurements in conjunction with traditional chemical techniques were used to assess in situ biodegradation of trichloroethylene (TCE) and carbon tetrachloride (CT). Vadose zone CHC, ethene, ethane, methane, O 2 , and CO 2 concentrations were analyzed using gas chromatography over 114 days at the Savannah River Site. δ 13 C of CHC and δ 13 C and 14 C of vadose zone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Usually intrinsic biodegradation by indigenous microbial populations is the key process for contaminant elimination and methods are required to demonstrate its efficacy. In groundwater studies, compound-specific isotope analysis (CSIA) has been used increasingly to demonstrate in situ biodegradation of various types of organic contaminants (Kelley et al, 1997;Sturchio et al, 1998;Hunkeler et al, 1999;Sherwood Lollar et al, 2001;Kolhatkar et al, 2002;Mancini et al, 2002;Meckenstock et al, 2002;Song et al, 2002;Kirtland et al, 2003;Richnow et al, 2003a,b;Chu et al, 2004;Griebler et al, 2004;Steinbach et al, 2004;Hunkeler et al, 2005;Morrill et al, 2005). In contrast, only a few studies have investigated the use of CSIA in the unsaturated zone (Stehmeier et al, 1999;Kirtland et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Usually intrinsic biodegradation by indigenous microbial populations is the key process for contaminant elimination and methods are required to demonstrate its efficacy. In groundwater studies, compound-specific isotope analysis (CSIA) has been used increasingly to demonstrate in situ biodegradation of various types of organic contaminants (Kelley et al, 1997;Sturchio et al, 1998;Hunkeler et al, 1999;Sherwood Lollar et al, 2001;Kolhatkar et al, 2002;Mancini et al, 2002;Meckenstock et al, 2002;Song et al, 2002;Kirtland et al, 2003;Richnow et al, 2003a,b;Chu et al, 2004;Griebler et al, 2004;Steinbach et al, 2004;Hunkeler et al, 2005;Morrill et al, 2005). In contrast, only a few studies have investigated the use of CSIA in the unsaturated zone (Stehmeier et al, 1999;Kirtland et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is thus possible to estimate the proportion of the entire CO 2 pool (respired carbon) attributable to the contaminant. Using solely this proportion, fossil-hydrocarbon or industrial chemical oxidation at field sites has been confirmed [7][8][9][10][11][12][13] . This proportion of contaminant derived CO 2 can then be coupled with total CO 2 mineralization rate (all CO 2 collected per unit time and volume) to determine intrinsic contaminant mineralization rate.…”
Section: Introductionmentioning
confidence: 95%
“…Because very distinct isotopic signatures are available in carbon-based contaminants, carbon isotopes have been recently applied to understanding contaminant attenuation processes at field sites [5][6][7][8][9][10][11][12][13] . Stable carbon isotopes can be used to determine if a source is attenuating based on Rayleigh distillation kinetics (c.f.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there are only few field CSIA studies dedicated to CMs. These studies are mainly based on carbon isotope measurements to confirm CT degradation in the non-saturated zone (Kirtland et al, 2003), to characterize the very depleted δ 13 C of CT and CF industrially produced from methane (Nijenhuis et al, 2013), to confirm CF degradation, along with concentration data, in a multi-contaminant polluted aquifer (Hunkeler et al, 2005) and/or to evaluate CF remediation treatment by alkaline hydrolysis in Òdena site (NE Spain) . New methods for chlorine isotope analyses of CMs and reference Λ values have only became available recently (Heckel et al, 2017a(Heckel et al, , 2017bTorrentó et al, 2017;Rodríguez-Fernández et al, 2018a, 2018b.…”
Section: Introductionmentioning
confidence: 99%